To study the efficacy of levonorgestrel intrauterine system in heavy menstrual bleeding - Vidya Gaikwad; Pankaj Salvi; G Harani Reddy; Nallani Veneela (New Indian Journal of OBGYN)
Background: Abnormal uterine bleeding (AUB) is the commonest symptom for which women seek gynaecologist’s consultation. The excessive blood loss interferes with woman’s social, emotional, physical and material quality of life. Medical treatments are preferred primary intervention though hysterectomy or endometrial ablation is the treatment of choice when medical treatment is ineffective or unacceptable. The levonorgestrel releasing intrauterine system (IUS) is a nonsurgical, long acting, alternative to the traditional medical and surgical treatments for heavy menstrual bleeding. Objectives: To assess the effectiveness of levonorgestrel IUS in heavy menstrual bleeding in terms of decreased menstruation and blood loss and to follow these patients for at least 2 years. Methods: A hospital based prospective, observational study was conducted with 35 patients from September 2019 - February 2021, to study the efficacy of levonorgestrel intra-uterine system (LNG - IUS) in the management of heavy menstrual bleeding. LNGIUS was inserted in post menstrual phase. Follow up was done at 3, 6, 12, 24 months. At each visit blood loss, menstrual pattern and opinion of women for satisfaction was recorded. Results: In first 3 months, 13 patients had irregular heavy bleeding and 11 had irregular spotting. 7 achieved normal menstrual cycle and 2 had scanty menstrual flow. During 6 months follow-up, 4 patients had irregular heavy bleeding and 3 had irregular spotting. 5 achieved normal menstrual cycle and 13 had scanty menstrual flow. 4 patients had achieved amenorrhoea, 9 experienced dysmenorrhoea. During 1 year follow-up, 2 patients had irregular spotting and 3 had scanty menstrual flow. 20 patients had achieved amenorrhoea while 1 experienced dysmenorrhoea. During 2 years follow-up, 1 patient had scanty menstrual flow and 9 patients had achieved amenorrhoea. There was significant reduction in the incidence of irregular heavy bleeding, irregular spotting and dysmenorrhoea and significantly higher number of patients achieved amenorrhoea as per chi-square test (p<0.05). Conclusion: LNG-IUS is an effective, long acting nonsurgical treatment for women with heavy menstrual bleeding. It can be a good alternative to hysterectomy for heavy menstrual bleeding due to many benign etiologies.